Physical Performance and Quality of Life in Older Adults: Is There Any Association between Them and Potential Drug Interactions in Polymedicated Octogenarians? - Verde, Zoraida (Int J Environ Res Public Health, 2019)
Older adults are at increased risk of several cytochrome P450 (CYP) drug interactions that can result in drug toxicity, reduced pharmacological effect, and adverse drug reactions. This study aimed to assess the prevalence of potential CYP interactions referring to the most clinically relevant drugs and exploring the relationship between them and quality of life and physical performance in Spanish octogenarians. Institutionalized and community-dwelling octogenarians (n = 102) treated at three primary care centers, were recruited by a research nurse. Anthropometric measurements, chronic diseases, prescribed drugs, quality of life, physical performance, mobility skills, hand grip strength and cognitive status data were collected. Potential CYP drug-drug interactions (DDIs) were selected referring to the main CYP implicated in their metabolism. The 72.2% of recruited octogenarians presented potentially inappropriate CYP inhibitor-substrate or CYP inductor-substrate combinations. Analyzing the EuroQol Visual Analogue scale (EQ-VAS) results, patients with a potential CYP DDI perceived worse health status than patients without it (p = 0.004). In addition, patients with a potential CYP DDI presented worse exercise capacity, kinesthetic abilities, or mobility than those who didn’t present a potential interaction (p = 0.01, p = 0.047, and p = 0.02, respectively). To investigate and control factors associated with loss of muscle strength and poor quality of life, polypharmacy and DDIs could help institutions in the management of physical frailty.